Identifying the factors affecting social welfare in Dong Nai Province, Vietnam today - Anh, Tran Tuan (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2024)
In the era of the Industrial Revolution 4.0, with appropriate socio-economic development policies, the economy of Vietnam in general, and Dong Nai Province in particular, has overcome difficult periods and achieved significant growth rates. This has led to a remarkable improvement in social welfare policies, contributing significantly to enhancing both the material and spiritual well-being of the community. This not only yields positive outcomes in ensuring the welfare of the people but also contributes to political stability and promotes economic growth. Therefore, identifying the factors affecting social welfare in Dong Nai Province, Vietnam today, and proposing solutions to leverage opportunities and overcome challenges in ensuring social welfare in the province, holds both theoretical and practical significance.